Turbo cola [videorecording (DVD)] - Covert, Luke; Oty, Samantha; Kiskis, Mathew; Stoesser, Nick; Spears, Jared; Denning, Jordyn; Tavernier, Landon; Oty, Samantha (Giant Interactive, 2022)
Austin Morris is foregoing the biggest party of the year to work overtime at the Quality Mart, much to the chagrin of his friends and new girlfriend, Mary Jane. What his friends don't know is that his true plan is to rob the store's ATM with his stoner side-kick, Swearsky, so that he can be with the girl of his dreams. This New Year's Eve ... 1999 ... will change everything.